THE CONCEPT OF MOKSA IN THE BOOK OF THE SANG HYANG BODHA STUDY OF HINDU PHILOSOPHY TEACHINGS IN BALI - Made Sri Putri Purnamawati (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Balinese Hinduism does not teach that life goals can only be achieved in life in another realm. Herein lies the main difference between the Teaching Sang Hyang Boodha concept of Moksa and the Vedic concept, Moksa being freedom from suffering, the destruction of egoism, greed, hatred and delusion. Based on this description, the author is very interested in researching the Philosophical Study of Moksa in the Sang Hyang Bodha in Bali. This type of research is a type of qualitative research. The data collection techniques in this study are; literature reviews, interviews, and documentation. In this study, the raw data that had been collected were processed using descriptive and qualitative methods. The concept of Moksa in the Sang Hyang Bodha in Bali is a very unique Balinese Hindu. Moksa is something that cannot be described in words because Moksa can only be understood by the wise. Moksa is in a definite state after craving disappears, fire is extinguished because it runs out of fuel as well as Moksa is the cessation of craving, attachment, passions and defilements. Moksa is the Eternal Truth, unborn, unperishable and unchanging. The philosophical study of Moksa in the Sang Hyang Bodha in Bali includes the study of Ontology, Epistemology and Axiology.